Effects of subcutaneous pasireotide on cardiac repolarization in healthy volunteers: A single‐center, phase I, randomized, four‐way crossover study. (16th November 2013) - Breitschaft, Astrid; Hu, Ke; Darstein, Christelle; Ligueros‐Saylan, Monica; Jordaan, Pierre; Song, Dongweon; Hudson, Michelle; Shah, Rashmi
Abstract The aim of this study was to evaluate the effects of subcutaneous pasireotide on cardiac repolarization in healthy volunteers. Healthy volunteers were randomized to one of four treatment sequences (n = 112) involving four successive treatments in different order: pasireotide 600 µg (therapeutic dose) or 1, 950 µg (maximum tolerated dose) bid by subcutaneous injection (sc), placebo injection and oral moxifloxacin. Maximum ΔΔQTcI occurred 2 hours post‐dose for both doses of pasireotide. Mean ΔΔQTcI was 13.2 milliseconds (90% CI: 11.4, 15.0) and 16.1 milliseconds (90% CI: 14.3, 17.9) for the 600 and 1, 950 µg bid doses, respectively. Maximal placebo‐subtracted change in QTcI from baseline for moxifloxacin was 11.1 (90% CI: 9.3, 12.9) milliseconds. Both pasireotide doses caused a reduction in heart rate: maximal heart rate change compared with placebo occurred at 1 hour for pasireotide 600 µg bid and at 0.5 hours for pasireotide 1, 950 µg bid, with heart rate reductions of 10.4 and 14.9 bpm, respectively. At the therapeutic dose of 600 µg, pasireotide has a modest QT‐prolonging effect. The relatively small increase of ∼3 milliseconds in ΔΔQTcI in the presence of a 3.25‐fold increase in dose suggests a relatively flat dose–effect relationship of pasireotide on ΔΔQTcI in healthy volunteers. No safety concerns for pasireotide were identified during the study.